Coal Tar Pitch Processing: Experimental and Theoretical Characteristics of Thermal Plasma Process Using DC Plasma Torch - Prado, E. S.P.; Essiptchouk, A. [UNESP]; Amaral-Labat, G.; da Silva Sobrinho, A. S.; Petraconi, G.; Baldan, M. R.; Miranda, F. S. [UNESP] (Springer Nature, 2023)
Thermal plasma-assisted processing is an effective process for the synthesis of gas (CO and H2) and carbonaceous materials production from industrial waste. In this paper, a DC plasma torch designed with two vortices chambers has been developed, and its characteristics have been experimentally tested. The plasma torch operates with different plasma working gases, including steam. The results of coal tar pitch (CTP) processing will be presented as a possible ecological application. CTP is a waste from the steel industry mainly composed of polycyclic aromatic hydrocarbons. The experimental results will be discussed with thermodynamic calculations and numerical simulation of the heat and mass transfer in the DC plasma torch and the chemical reaction chamber. The simulations were carried out to clarify the regions of gas flow and temperatures for producing synthesis gas and carbon nanomaterial. The results enable one to predict the produced gas composition and carbon nanomaterial properties. The physicochemical properties of carbon nanomaterial and synthesis gas show high efficiency in converting CTP into high-value-added products.
Keywords: Coal tar pitch; Numerical simulation; Thermal plasma; Thermodynamic calculation